Dehydrocorydaline attenuates bleomycin-induced pulmonary fibrosis by inhibiting fibroblast activation - Jianhan He; Huihui Yue; Shufei Zhang; Ruihan Dong; Fengqin Zhang; Xuewen Wang; Ke Wang; Huilan Zhang; Danlei Yang; Zhaoxing Dong; Huiguo Liu (Respiratory Research)
Abstract Background Pulmonary fibrosis (PF) is an irreversible, progressive, chronic and fatal interstitial lung disease with limited therapeutic options. Dehydrocorydaline (DHC), derived from the traditional Chinese medicinal plant Corydalis yanhusuo, has exhibited a variety of pharmacological properties. Nevertheless, the potential function and mechanism of DHC in the management of PF have yet to be elucidated. Purpose To evaluate the therapeutical efficacy of DHC in different PF models and elucidate its underlying mechanism. Methods A well-established Bleomycin-induced PF mouse model and human precision-cut lung slices (hPCLS) following fibrosis-inducing cocktail stimulation were employed. The antifibrotic effects of DHC on PF were measured by histopathological manifestation, immunofluorescent staining and expression levels of fibrosis related markers. Human primary pulmonary fibroblasts (HPFs) were used to explore the impact of DHC on fibroblast function and the underlying mechanism. Results Here, we demonstrated that DHC exhibited a therapeutic efficacy in Bleomycin-induced PF mouse model with a dose dependent, as well as in hPCLS after fibrosis-inducing cocktail stimulation, as evidenced by histopathological staining, decrease of Fibronectin, Collagen 1 and α-SMA expression. Additionally, in vitro experiments indicated that DHC effectively suppressed fibroblast to myofibroblast transition, but had no significant effect on the proliferation and migration of fibroblast. Mechanistic studies revealed that the inhibitory effect of DHC on fibroblast activation was dependent on the endoplasmic reticulum stress, thereby inhibiting TGF-β/SMAD signal pathway. Conclusions Our study implied that DHC hold a promise therapeutic approach against PF by suppressing fibroblast activation. The safety and efficacy of DHC have been preliminary demonstrated in a mouse model. Graphical Abstract